The dynamics of smallholder farmers’ acquisition and distribution of sweetpotato vines in the Lake Victoria Zone Region, Tanzania - Adam, R.I.; Badstue, L.; Sindi, K. (Springer, 2018)
This paper offers new insights into smallholder farmer’s practices regarding acquisition and distribution of sweetpotato planting material in the Mwanza and Mara regions of Tanzania by examining three specific issues: (i) farmers’ sources of planting material; (ii) factors that influence farmers’ sourcing of planting materials outside their own farms and (iii) the types of transactions and social relations involved in farmers’ acquisition and distribution of sweetpotato planting material. Data were collected using mixed methods, including a survey of 621 households across nine districts, semi-structured key informant interviews with 28 women sweetpotato farmers, and six focus group discussions. Findings show that farmers in the study area rely almost exclusively on informal seed systems, and that the majority (> 56%) produce their own planting material. Individual, household and community level factors influence farmers’ acquisition of planting materials outside their own farms. The sources and mode of transaction related to acquisition/distribution of planting material are strongly influenced by the type of social relationship between the parties involved. Strong social ties facilitate the majority of local planting material acquisitions/distributions, and favor provision of locally available planting material as a gift/without payment. Weak social ties are primarily associated with the transaction modality of purchase/sale, and frequently help facilitate acquisition of new or exotic planting material. The findings provide entry points both for entities that seek to enhance small-scale farmers’ access to improved, high quality sweetpotato germplasm, as well as broader efforts to strengthen research and development strategies for integrating formal and informal seed systems.